Grape seed proanthocyanidin extract induces apoptotic and autophagic cell death in rheumatoid arthritis fibroblast-like synoviocytes - Ye-Rin Heo,; Chang-Nam Son,; Won-Ki Baek,; Sang-Hyon Kim, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to evaluate the association between grape seed proanthocyanidin extract (GSPE) and rheumatoid arthritis-fibroblast-like synoviocytes (RA-FLSs) and to investigate whether GSPE induces cell death in RA-FLSs. Materials and methods: The FLSs were isolated from RA synovial tissues. Cell viability and cell cycle staging were analyzed using a hemocytometer and flow cytometry. Caspase 3 and poly (ADP-ribose) polymerase (PARP) proteins were analyzed using Western blotting with z-VAD-fmk. Protein LC3 and polyubiquitin-binding protein p62 that were degraded by autophagy were evaluated using Western blotting with 3-methyladenine and chloroquine. Reactive oxygen species (ROS) were also evaluated. Results: When RA-FLSs were treated with GSPE, cell viability decreased, the number of cells in sub-G1 and G2/M phases increased, and the expression of pro-PARP and pro-caspase 3 proteins decreased in a concentration-dependent manner. This result was offset, when the cells were co-treated with the pan-caspase inhibitor z-VAD-fmk. The reduced cell viability, increased expression of LC3-II protein, and reduced expression of p62 protein with GSPE treatment were offset, when RA-FLSs were co-treated with GSPE and autophagy inhibitors 3-methyladenine and chloroquine. The level of ROS in RA-FLSs treated with GSPE was significantly lower than treatment with N-acetyl-cysteine, a ROS inhibitor. Conclusion: Our study results show that GSPE induces apoptotic and autophagic cell death and inhibites reactive oxygen species in RA-FLSs.